The Physical Activity Level of Ophthalmologists at Work: A Pedometer-Based Study. (January 2023) - Assayag, Elishai; Wiener, Rony; Gelman, Evgeny; Abulafia, Adi; Wasser, Lauren M.; Hanhart, Joel; Zadok, David; Weill, Yishay
Background: Ophthalmology practice entails many hours of physical inactivity, a potential long-term health hazard. This study aims to perform a pedometer-based evaluation of the physical activity (PA) levels of ophthalmologists at work. Methods: This is a prospective observational study. Ophthalmologists from a single tertiary medical center were monitored with electronic pedometers during six morning sessions in the ophthalmology clinics. Working hours and the number of patients seen per clinic session were retrieved. The age and body mass index (BMI) of participants were documented. Step number per working hour (SPH) was calculated for all participants. Comparisons between males and females, practicing ophthalmologists (attendings) and ophthalmology residents (residents), and sub-specialties were performed. Correlations between SPH and age, BMI, and patients seen per clinic session were computed. Findings: Pedometer readings for a total of 673 working hours were analyzed for 24 ophthalmologists, 17% female, 17 attendings, mean age 44.2 years (standard deviation ( SD = 9.8). The average number of SPH for all participants was 359.7 ( SD = 166.7). The mean PA level of residents was significantly higher than that of attendings (410.17 SPH vs. 338.95 SPH, respectively, p = .019). Oculoplastic surgeons demonstrated significantly higher step counts per hour than cornea specialists (439.90 SPH vs. 245.55 SPH, respectively, p = .002). A negative correlation was observed between SPH and the number of patients seen per clinic session ( ρ = −0.274, p = .001). Conclusions/Applications to Practice: Low number of SPH for ophthalmologists in this study indicates ophthalmology to be a highly sedentary medical occupation. PA levels of ophthalmologists in the workplace may indicate a personal health care challenge.